Simulação computacional da altura e temperatura da camada de fumaça - Lucimar de Oliveira Meira (2017)
The main objective of this work is the computational simulation of the height of the interface of the smoke layer - AICF and the average temperature of the smoke layer - TMCF, in environments in fire situation with different configurations of smoke control systems. For the development of the work, the FDS, CFAST and B-RISK programs were used. Among the studied systems were analyzed situations with air inlets and natural or mechanical smoke exits. It is concluded that, in general, the results found with the FDS, CFAST and B-RISK programs were close to the experimental results and simulations of other authors, sometimes more conservative, at least. In cases where there are air inlets located in the smoke layer, the zone programs, CFAST and B-RISK, present a divergent result from that observed experimentally and therefore should not be used to analyze these situations. From the comparisons of the results of the simulations with the procedures found in the Technical Instructions, it is concluded that the procedures are very safe and changes are necessary to become more economical. The simulations developed in this work can help to carry out analyzes, projects and experiments, evaluating more accurately the effect of the smoke in the evacuation time of the users and the temperature in the structure of the building.